Use of AMD3100 for Bone Marrow Derived Mesenchymal Stem Cells Mobilization in the Treatment of Murine Asherman's Syndrome - Flores, V A; Delis, P A; Mamillapalli, R; Taylor, H S (F&S Science (Online), 2025)
Asherman's syndrome (AS) is characterized by intrauterine adhesions/fibrosis, resulting from damage to the endometrial basalis layer. The consequences of AS include infertility, recurrent pregnancy loss, preterm rupture of membranes, and placental abruption. Hysteroscopic adhesiolysis does not consistently restore endometrial function; there is a need for more effective treatments. Bone marrow-derived mesenchymal stem cells (BM-MSCs) circulate systemically and contribute to tissue repair/regeneration, suggesting they may serve as a source of progenitor cells for endometrial regeneration. Increasing the supply of BM-MSCs to the endometrium may treat AS by allowing for regeneration/replenishment of endometrial progenitor cells. Mobilization of autologous BM-MSCs using AMD3100, a CXC-motif-receptor-4 antagonist, is approved for bone marrow transplantation. We aimed to determine if the optimal timing of AMD 3100 administration-based on CXCL12 production-would better recruit BM-MSCs in a murine model of severe AS, and restore functioning endometrium/fertility. Severe AS Murine Model SUBJECTS: C57BL/6 mice in the diestrus phase undergoing surgical AS induction. Single injection with AMD3100 (treatment) or vehicle (saline). AMD3100 administration timing was based on the determination of maximum CXCL12 release following AS induction. Mice were then mated. Time to pregnancy, litter size, and miscarriage rate. Maximum uterine CXCL12 production occurred 48hrs following AS induction, thus AMD3100 vs. saline was administered 48hrs following induction. Of the AMD3100 treated mice, all achieved pregnancy and delivered. The treatment group became pregnant and delivered significantly sooner, indicating a faster time to conception (20 vs. 26 days). The treatment group had significantly larger litter sizes (6.5 vs. 4.2 pups), and significantly more live pups at delivery compared to the control group (6.0 vs. 2.7). AMD3100 had a significant effect on uterine repair and regeneration in AS. The likelihood of pregnancy was significantly higher and more rapid in AS mice treated with AMD3100. Treated mice also had larger litter sizes and fewer miscarriages when compared to controls. Furthermore, we determined for the first time the levels of CXCL12 in uteri following uterine injury, which allowed for the determination of the optimal timing of AMD3100 administration, to ensure mobilized BMD-MSCs homed to the uterus.